Molecular Biology in Cellular Pathology 2003
DOI: 10.1002/0470867949.ch12
|View full text |Cite
|
Sign up to set email alerts
|

TaqMan® Technology and Real‐Time Polymerase Chain Reaction

Abstract: Twenty-eight PIC male piglets (similar birth and parity, weaned at 21±1.5 days) were used to study the effect of the different sources of dietary starch on the number of Bifidobacteria in the digesta of the duodenum, jejunum, ileum, cecum and colon. Pigs were randomly assigned to one of four diets formulated with corn starch, wheat starch, tapioca or pea starch. The determined ratio of amylose to amylopectin for these starches was 0.21, 0.24, 0.12 and 0.52, respectively based on the 16s rRNA sequences of maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Quantitative Real-Time PCR Reactions. In this collaborative ring trial, we adopted the quantitative real-time PCR primers reported in our previous study and employed a new TaqMan probe with complementary sequence as our previous reported probe because there was a G at the 5 0 end of the previous probe (25 ), which could affect the signal intensity of fluorescence (dada not shown) (36 ). The sequences and locations of quantitative primers (SPS-1F/3R) together with the modified probe (SPS-P) are presented in Table 1 and Participants were requested to dilute each of these four DNA samples to the concentration of 10, 1, 0.1, 0.01, or 0.002 ng/μL by using the DNA solution provided.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative Real-Time PCR Reactions. In this collaborative ring trial, we adopted the quantitative real-time PCR primers reported in our previous study and employed a new TaqMan probe with complementary sequence as our previous reported probe because there was a G at the 5 0 end of the previous probe (25 ), which could affect the signal intensity of fluorescence (dada not shown) (36 ). The sequences and locations of quantitative primers (SPS-1F/3R) together with the modified probe (SPS-P) are presented in Table 1 and Participants were requested to dilute each of these four DNA samples to the concentration of 10, 1, 0.1, 0.01, or 0.002 ng/μL by using the DNA solution provided.…”
Section: Methodsmentioning
confidence: 99%
“…The development of multiplexed array-based high-throughput genotyping technologies [21] or uniplex SNP genotyping platforms, such as TaqMan TM [22] and KASP TM , among others, has greatly facilitated the use of SNP markers. Kompetitive Allele Specific PCR or KASP TM is a cost-effective technology with high sensitivity, accuracy and flexibility allowing genotyping either few samples with many SNP markers or several samples with few SNP markers in a single plate [11].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, RT-PCR is based upon the generation of a fluorescent signal during the PCR process, which is detected during cycling and reflects the amount of PCR product synthesized during the reaction. 33 RT-PCR has better sensitivity than Sanger sequencing but only identifies mutations that the sequence specific primer is designed to detect. 32 PCR-based methods are also utilized to detect candidate genes as a research tool in validating genes discovered through genome-wide association studies.…”
Section: Common Molecular Profiling Methodologiesmentioning
confidence: 99%